KNOWLEDGE ECONOMY IN THE SYSTEM OF CONTINUOUS EDUCATION OF UKRAINE - Burunova Оlena; Gushko, Sergii; Kulishov, Volodymyr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article investigates the issues and challenges associated with the variability, mobility of technologies of education, development of the conceptual framework based on modernization of economic education, formation of professional knowledge of future specialists of an economic profile in the system of continuous economic education in the conditions of the educational and scientific complex “school-college-university” and the ability economically expedient of such system of knowledge. The economic efficiency of the system of professional knowledge could be achieved through a scientific justification of the project-creative component that is not investigated enough. And there is necessity to implement this experimental innovative component of the professional economic training.In the process of the research the authors worked out a theoretical cluster system model of knowledge-based economy by applying latest innovative technologies where intersubjective innovative connections are available. The research results involve clarification of the following concepts essence “modernisation of the system of professional knowledge in economics” and “future specialists in the sphere of economics”; introduction of a project-creative approach in an educational-scientific complex “a school with its economic specialization – a college of economics – a university of economics” under conditions of continuous economic education.